Quantifying archaeology - Shennan, Stephen (Edinburgh University Press, 1997)
The second edition of this textbook introduces archaeology students to the use of statistics in their subject. Based on the author's long-running undergraduate course, this new edition includes a wider range of topics presented in greater depth.